Exploring the Interconnectedness Between Knowledge Level and Profile Traits of Cluster Frontline Demonstration-pulse Farmers - Vamshi, M.; Veni, C. P.; Naik, V. R.; Mathangi , Sumana Sri (International Journal of Bio-resource and Stress Management, 2025)
A study was conducted during March, 2022 in Central Telangana Zone, India to measure the knowledge level of Cluster Frontline Demonstration (CFLD)-Pulse farmers by constructing a Knowledge Test battery. Relevant items were collected from review of literature, publications, and discussions with subject matter specialists’ of Krishi Vigyan Kendra and concerned scientists of related fields. Item analysis was done by item difficulty index, item discrimination index and point biserial correlation and 22 items were finalized for knowledge test. The test was administered to 160 respondents (100 beneficiary and 60 non-beneficiary farmers) of the CFLD programme conducted by Krishi Vigyan Kendra Wyra and Malyal belonging to Khammam and Mahabubabad Districts of Telangana state respectively (50 beneficiary and 30 non-beneficiary farmers from each KVK). Majority of the Cluster Frontline Demonstration-beneficiaries (59%) and (50%) of non-beneficiaries were in medium knowledge category. To further validate the factors that were influencing the knowledge gain in the respondents, a correlation between profile traits of respondents and their knowledge level was carried out and further multinomial model test was carried out to validate the result. Individual factors/profile traits influencing knowledge gain were Cosmopoliteness, Resource availability and, Risk taking ability for beneficiary farmers and Cosmopoliteness followed by economic motivation for non-beneficiary farmers. Multinomial model results confirmed that these were determining factors that played major role in knowledge of farmers.